Electronic Effects on Chiral NHC-Transition-Metal Catalysis - Yong, Xuefeng; Thurston, Ryan; Ho, Chun Yu (Synthesis (Germany), 2019)
Though the properties of N-heterocyclic carbenes (NHCs) are generally dominated by the very strong σ donating character, electronic activation has emerged as an effective method to cooperate with typical carbon-framework steric optimization for highly enantioselective chiral NHC-transition-metal catalysis in recent years. NHC electronic changes associated with structural variations are now better understood by quantitative analysis using various methods. Here we highlighted and correlated some interesting chiral induction improvement methods, which were brought by electronic and steric cooperation on chiral NHC-transition-metal catalysis. 1 Introduction 2 Hemilabile Sidechains on NHC Ligands 3 Electronic and Bond Angle Changes Brought by NHC Core Size Variations 4 Electronic Activators on the NHC Core 5 Conjugated Systems and Fused Ring Structures 6 Remote Electronic Activators on the N -Aryl Ring 7 Summary and Outlook.
CRIS-Team Scopus Importer:2019-05-17
Keywords: chiral N-heterocyclic carbenes; electronic effect; enantioselective synthesis; transition-metal catalysis